(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Chaiphongpachara T, Sumruayphol S. 2019. Geometric morphometrics as a tool for three species identification of the firefly (Coleoptera: Lampyridae) in Thailand. Biodiversitas 20: 2388-2395. Firefly is an insect belonging to the Lampyridae family that is important to the ecosystem, generates income from tourism in the area and act as a biological control for snail, an intermediate hosts of trematode parasites. Some types of the firefly, it is difficult to distinguish the species using standard methods because of similarities in morphology while the external characteristics of specimens are damaged during collection, presenting an obstacle to species identification. This study used geometric morphometrics (GM) for identification of firefly species. Samples collection was conducted in the rainy season from August to October 2015 in three districts of Samut Songkham province, Thailand. A total of 200 and 157 fireflies from 3 genera and four species, including Luciola aquatilis Thancharoen, Pteroptyx valida Olivier, Pteroptyx malaccae Gorham and Pyrocoelia praetexta Olivier were used for landmark-based and outline-based GM analysis, respectively. The results showed that both types of GM analysis produced similar results, size variation between two firefly pairs was not statistically significant, including female L. aquatilis with male P. praetexta, and female P. valida with male P. valida. Both landmark-based and outline-based GM methods can distinguish the shape for each type of firefly with high accuracy, especially the outline-based GM method. This result was supported by reclassification scores. According to our findings, the GM can be used to separate species of firefly with high efficiency. Therefore, this GM method represents one way of overcoming difficulties with firefly identification and can support future studies of fireflies.